The Digital Frontier of Accounting: Unraveling The Impact of Digital Literacy and Technology Adoption - Ifada, Luluk Muhimatul; Mutoharoh, Mutoharoh; Indriastuti, Maya; Indarti, Maria Goretti Kentris (Faculty of Economics and Business, Universitas Negeri Yogyakarta in collaboration with the Institute for, 2025)
AbstractThis study aims to examine the relationship between digital literacy, information and technology literacy in relation to digitalization in accounting and how the technology adoption mediates these relationships. Through quantitative approach, questionnaires were distributed to the auditors of the public accounting firms in Semarang City using non-probability sampling method. In this study, multiple regression analysis is used to predict partially or simultaneously the effect of independent variables on the dependent variable. The statistical results show that digital literacy, information and technology literacy have a positive and significant relationship with digitalization in the accounting profession. In contrast, digital literacy has no effect on the technology adoption, while the technology adoption has a positive and significant effect on digitalization in the accounting profession.